Opium and grade of urothelial bladder cancer - Shahryar Zeighami; Entegham Azizzadeh; Hamid Reza Tabatabaee; Ali Adib; Amir Hossein Babaei; Ali Ariafar (Society of Diabetic Nephropathy Prevention, 2018)
Background: Bladder cancer is a serious global problem. Although the risk factors of bladder cancer have been found through many studies, the effect of them on the grade of this cancer has not been focused previously. Objectives: This study was conducted to evaluate the association of some risk factors of urothelial bladder cancer on its grade. Patients and Methods: The patients with proved diagnosis of urothelial carcinoma of bladder were enrolled in this study. They were divided into case group (those with high-grade bladder cancer) and control group (those with low-grade bladder cancer). Each of case and control groups contained 103 patients. Age, gender, place of residence, cigarette smoking state, opium consumption state, occupation, previous exposure to poisons or chemicals, and family history of bladder cancer were compared between the case and control groups. Results: Eighty-two patients (79.6%) of the case group and 87(84.5%) of the control group were male. The mean age of the case group was significantly higher than control group (66.1±11.8 and 61.7±14.2, respectively; P=0.003). The results of this study showed that ever usage of opium was significantly higher in the case group (OR=2.97; 95% CI: 1.64- 5.38; P <0.001). Although mean pack-years of cigarette smoking of case group was significantly higher than control group in univariate analysis (P=0.009), it was omitted from regression models when multivariate analysis was applied. Conclusions: High grade urothelial bladder cancer has been significantly associated with opium usage and older ages